2015
DOI: 10.2106/jbjs.n.00523
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cell Phones as a Potential Source of Bacterial Contamination in the Operating Room

Abstract: The current study investigates orthopaedic surgeons' cell phones as a potential source of nosocomial infection in the operating room. On the basis of the high percentage of cell phone contamination found, we would recommend periodic cell phone cleaning with either the wipes used in our study or similar ones. In addition, given that there was a high contamination rate one week after disinfection, we would recommend considering cell phone cleaning more frequently than once a week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 15 publications
3
59
0
3
Order By: Relevance
“…by Selim et al showed the most common microorganisms on healthcare worker's cell phones were MRSA and Staphylococcus coagulase negative (13). Other similar studies also reported Pseudomonas species in addition to previous germs (12)(13)(14)(15). In 2012, Ustun et al reported that among 183 samples that were collected from cell phones of physicians, nurses and laboratory staffs, 179 (97.8%) were contaminated including Extended Spectrum Beta-Lactamases (ESBLs) producing E. coli (11.2%) and MRSA (9.5%) (16).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…by Selim et al showed the most common microorganisms on healthcare worker's cell phones were MRSA and Staphylococcus coagulase negative (13). Other similar studies also reported Pseudomonas species in addition to previous germs (12)(13)(14)(15). In 2012, Ustun et al reported that among 183 samples that were collected from cell phones of physicians, nurses and laboratory staffs, 179 (97.8%) were contaminated including Extended Spectrum Beta-Lactamases (ESBLs) producing E. coli (11.2%) and MRSA (9.5%) (16).…”
Section: Discussionmentioning
confidence: 92%
“…In 2010, El kholy et al reported contamination of mobile phones with E. coli, pseudomonas aeruginosa, Proteus vulgaris, Klebsiella, Serratia and Staphylococcus aureus (2). Some studies reported other microorganisms such as Acinetobacter and Enterococcus faecalis (1,15,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…The process may include cleaning or containing the item or placing the item in a designated location. Research indicates that personal communication devices (eg, cell phones, tablets) are highly contaminated with microorganisms, including those that may be pathogenic . Before bringing personal electronic devices into the OR, perioperative personnel should clean them according to the device manufacturer's instructions for use .…”
Section: Practice Point: Personal Itemsmentioning
confidence: 99%
“…Researchers can measure surface contamination by culturing specific microorganisms; assessing CFUs, adenosine triphosphate (ATP), and relative light units (RLUs); visually inspecting surfaces; and using fluorescent marking gel with allocation‐of‐contamination ratings 5,7,9,13,15,40,46‐50 . Microorganisms identified in a few of the studies that examined surface contamination included S aureus , methicillin‐resistant S aureus , S epidermidis , Enterobacter , Acinetobacter species, and Pseudomonas species 19,47‐49,51,52 …”
Section: Airborne Sources and Control Of Contaminantsmentioning
confidence: 99%
“…Decontamination significantly reduced the colony count from 258 CFUs before decontamination to 127 CFUs after decontamination ( P = .0001). Shakir et al 51 used ATP to quantify organic matter and cultured the mobile phones of orthopedic attending surgeons and residents before cleaning and retesting the phones. Before disinfection, the mean ATP reading was 3,488 ± 1,699 RLUs; after cleaning, the mean ATP reading was 200 ± 123 RLUs, with a decrease in pathogenic bacteria from 83% before disinfection to 8% after disinfection (N = 53).…”
Section: Airborne Sources and Control Of Contaminantsmentioning
confidence: 99%